BRG1, INI1, and ARID1B Deficiency in Endometrial Carcinoma: A Clinicopathologic and Immunohistochemical Analysis of a Large Series From a Single Institution. (December 2020) - Kihara, Atsushi; Amano, Yusuke; Matsubara, Daisuke; Fukushima, Noriyoshi; Fujiwara, Hiroyuki; Niki, Toshiro
Abstract : Switch/sucrose nonfermenting complex subunits, such as BRG1, INI1, and ARID1B, are inactivated in a subset of endometrial undifferentiated carcinoma and dedifferentiated carcinoma (DC). Limited information is currently available on their prevalence in other subtypes or the nosological status of endometrial carcinoma with their deficiencies. This study immunohistochemically examined the expression status of BRG1, INI1, and ARID1B using 570 archived cases of endometrial carcinoma and carcinosarcoma resected at a single institution. We identified 1 BRG1-deficient undifferentiated carcinoma, 8 BRG1/INI1/ARID1B–deficient DC, and 3 BRG1-deficient clear-cell carcinomas. None of the cases of endometrioid and serous carcinomas or carcinosarcoma showed deficiencies of these subunits. We then compared 8 BRG1/INI1/ARID1B–deficient DC with 6 BRG1/INI1/ARID1B–intact DC and 28 carcinosarcomas, the latter of which was often confused with DC. Histologically, BRG1/INI1/ARID1B–intact and BRG1/INI1/ARID1B–deficient DC shared a monotonous solid appearance with rhabdoid and epithelioid cells and a myxoid stroma; however, abrupt keratinization and cell spindling was absent in BRG1/INI1/ARID1B–deficient tumors. The median overall survival of patients with BRG1/INI1/ARID1B–deficient DC was 3.8 months, which was worse than those with BRG1/INI1/ARID1B–intact DC ( P =0.008) and with carcinosarcoma ( P =0.004). BRG1/INI1/ARID1B–deficient DC may be a separate entity with an aggressive behavior to be distinguished from BRG1/INI1/ARID1B–intact DC and carcinosarcoma. Regarding clear-cell carcinoma (n=12), BRG1 deficiency appeared to be mutually exclusive with abnormal ARID1A, BRM, and p53 expression. Further studies are needed to clarify whether BRG1 deficiency plays a role in the pathogenesis of clear-cell carcinoma. Abstract : Supplemental Digital Content is available in the text.